Gambaran Kepuasan Pasien terhadap Pelayanan Klinik Perioperatif Terintegrasi di RSUP Prof. Dr. R. D. Kandou - Datu, Muliana E.; Kumaat, Lucky T.; Kambey, Barry I. (e-CliniC, 2019)
Abstract: Satisfaction is closely related with expected service and reality of the service available at the hospital. Satisfaction will be achieved if the performance is in line with the expectation of the patient. This study was aimed to obtain an overview of patient satisfaction towards the service provided by the Integrated Perioperative Clinic of Prof. Dr. R. D. Kandou Hospital. This was a descriptive study using questionnaire. Respondents were patients/families who received services at the clinic. The results showed a total of 100 respondents involved in this study, consisting of 30 females (30%) and 70 males (70%). Most respondents aged early to late adulthood numbering as many as 46 respondents (46%). The majority of respondents numbering 44 respondents (44%) had high school education level. Based on the analysis, high calculation results were obtained categorized as very good or very satisfied. In conclusion, the level of patient satisfaction towards the service provided by the Integrated Perioperative Clinic of Prof. R. D. Kandou Central Hospital based on the quality of service scale measuring direct evidence (tangibles), reliability, comprehension (responsiveness), assurance, and empathy was very high. It means that patients are very satisfied with the services provided by the clinic.Keywords: patient satisfaction, quality of service, perioperative clinicÂ Abstrak: Kepuasan sangat berkaitan dengan pelayanan yang diharapkan dan kenyataan pelayanan yang telah diberikan di rumah sakit. Kepuasan akan terpenuhi bila pelayanan yang diberikan dirasakan telah sesuai dengan harapan pasien. Penelitian ini bertujuan untuk mengetahui gambaran kepuasan pasien terhadap pelayanan klinik perioperatif terintegrasi di RSUP Prof Dr. R. D. Kandou. Jenis penelitian ialah deskriptif dengan menggunakan kuesio-ner. Responden penelitian ialah pasien yang mendapatkan pelayanan di klinik perioperatif. Hasil penelitian mendapatkan total 100 responden yang terdiri dari 30 orang perempuan (30%) dan 70 orang laki-laki (70%). Responden berusia dewasa awal dan dewasa akhir yang terbanyak yaitu 46 orang (46%). Sebagian besar responden memiliki tingkat pendidikan SMA sebanyak 44 orang (44%). Hasil analisis mendapatkan hasil perhitungan yang tinggi dan masuk dalam kategori sangat baik atau sangat puas. Simpulan penelitian ini ialah tingkat kepuasan pasien terhadap pelayanan klinik perioperatif terintegrasi di RSUP Prof. Dr. R. D. Kandou Manado berdasarkan skala kualitas pelayanan yaitu bukti langsung (tangibles), kehandalan (reliability), daya tangkap (responsiveness), jaminan (assurance), dan empati (empathy) sangat tinggi yang berarti pasien merasa sangat puas atas pelayanan yang diberikan oleh klinik perioperatif terintegrasi.Kata kunci: kepuasan pasien, kualitas pelayanan, klinik perioperatif